Apropriação de aspectos culturais e linguísticos no ensino de língua estrangeira moderna através de animações cinematográficas hispânicas - Leandro, Thiago Vidal (2023)
This work aims to provide mechanisms that provide the appropriation of cultural and linguistic aspects in the teaching of modern foreign language – Spanish through didactic sequences based on Hispanic cinematographic animations, aimed at basic education teachers. To this end, we present theoretical-methodological reflections on the teaching of foreign languages based on applied linguistics raised by Rojo (2007), Rodrigues (2011), Cavalcanti (1986), Soares (2008), Moita Lopes (1996) and especially with Cerutti-Rizatti (2008). In the theoretical-methodological aspect, we carried out an action research. As research instruments, we used a diagnostic test and application of 13 (thirteen) didactic sequences that aimed to contribute to the review and deepening of sociocultural contents present in countries such as Spain, Mexico and Colombia in 1st year high school classes of a state public vocational school, located in the city of Barbalha-CE. The experience report and the material developed and applied by the author contribute to broaden the field of sociocultural perception of the 120 (one hundred and twenty) students involved.